2009
DOI: 10.1093/schbul/sbp123
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Interacts With Expressed Emotion Criticism in the Prediction of Psychotic Symptom Exacerbation

Abstract: Psychotic symptoms are exacerbated by social stressors in schizophrenia and schizoaffective disorder patients as a group. More specifically, critical attitudes toward patients on the part of family members and others have been associated with a higher risk of relapse in the patients. Some patients appear to be especially vulnerable in this regard. One variable that could affect the degree of sensitivity to a social stressor such as criticism is the individual's level of anxiety. The present longitudinal study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
(72 reference statements)
0
19
0
3
Order By: Relevance
“…Findings in the broader schizophrenia-spectrum literature also suggested that FIp improves levels of EE (Pharoah et al, 2010), however this included emotional over-involvement. Criticism from carers has been positively associated with increases in levels of anxiety in service users (Kuipers et al, 2006; Docherty et al, 2011). The reductions in criticism remains important given its predictive role in subsequent relapse (Bebbington and Kuipers, 1994) and adverse impact on patient well-being including at a neural level (Rylands et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the broader schizophrenia-spectrum literature also suggested that FIp improves levels of EE (Pharoah et al, 2010), however this included emotional over-involvement. Criticism from carers has been positively associated with increases in levels of anxiety in service users (Kuipers et al, 2006; Docherty et al, 2011). The reductions in criticism remains important given its predictive role in subsequent relapse (Bebbington and Kuipers, 1994) and adverse impact on patient well-being including at a neural level (Rylands et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high NEE in close relatives increases the likelihood of psychiatric relapse (Brown and Rutter 1966;Bebbington and Kuipers 1994). In patients with psychosis, a high level of relative criticism is related to longer hospital stay (Marom et al 2005) and high depression and anxiety in patients (Docherty et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, CFI-data from relatives was not reported. In a longitudinal study, 27 relatively stable outpatients with schizophrenia or schizoaffective disorder filled in PCS and the single "most influential other" (MIO) person was interviewed with CFI [28]. Patient ratings on the perceived criticism item were significantly related to the high vs low CFI criticism ratings (p = 0.03).…”
Section: Comparison Of Feers With Alternative Studies Of Patient Percmentioning
confidence: 99%